Employee share ownership as moderator of the relationship between firm-specific human capital investments and organizational commitment - Eric Kaarsemaker (Management Revue, 2008)
Tight labour markets and changing employment relationships make employees with high levels of firm-specific knowledge, skills, and abilities less dependent on and committed to their employer. Companies need to work harder in order to attract and retain employees and protect their mutual human capital investments. Using a dataset with survey data from employees in 11 companies (N = 777), the present study shows evidence that employee share ownership, provided that it is taken seriously as reflected by the presence of a small number of other HRM practices in the company, might be a worthwhile avenue for managers to explore.
Keywords: 650; human resource management; employee share ownership; organizational effectiveness; firm-specific investments